Descriptive Study On The Teacher’s View and Students' Opinion On The Use Of Visual Aids - hariyanto, Muhammad (Al Iman: Jurnal Keislaman dan Kemasyarakatan, 2019)
This research is conducted in order to investigate the teacher view and the students' opinion on the use of visual aid in teaching learning activities. This research was conducted using a qualitative approach. The data was gained by using an open-ended questionnaire. The location of this research was at MTs. Afifiyah Pragaan Sumenep. The target of the research was the 22 students in seventh grade and their English teacher at MTs.Afifiyah Pragaan Sumenep. After accomplishing the finding and discussion of research, it can be concluded that the use of visual aids at MTs. Afifiyah Pragaan Sumenep enhances the students' performance in the teaching-learning process. Visual aids argue can produce a positive contribution to the students leaning performances. Although there are some problems faced by the teacher in using a visual aid, the teacher still makes English teaching-learning process in classroom successfully and efficiently. However, the problems in apply the visual aid can enhance not only for the student’s performance in learning but also for the teacher to progress their quality in teaching-learning procedures. Related to this study, a visual aid is recommended as one of many illustrators that can be used by the teacher to become an alternative tool to help some difficulties found in teaching learning activities. Penelitian ini dilakukan untuk menyelidiki pandangan guru dan pendapat siswa tentang penggunaan alat bantu visual dalam kegiatan belajar mengajar. Penelitian ini dilakukan dengan menggunakan pendekatan kualitatif. Data diperoleh dengan menggunakan kuesioner terbuka. Lokasi penelitian ini adalah di MTs. Afifiyah Pragaan Sumenep. Sasaran penelitian adalah 22 siswa di kelas tujuh dan guru bahasa Inggris mereka di MTs.Afifiyah Pragaan Sumenep. Setelah menyelesaikan temuan dan diskusi penelitian, dapat disimpulkan bahwa penggunaan alat bantu visual di MTs. Afifiyah Pragaan Sumenep meningkatkan kinerja siswa dalam proses belajar-mengajar. Alat bantu visual dapat menghasilkan kontribusi positif bagi siswa yang condong pada kinerja. Meskipun ada beberapa masalah yang dihadapi oleh guru dalam menggunakan alat bantu visual, guru tetap membuat proses belajar-mengajar bahasa Inggris di kelas berhasil dan efisien. Bagaimanapun, masalah dalam menerapkan alat bantu visual tidak hanya untuk meningkatkan kinerja siswa dalam pembelajaran tetapi juga bagi guru untuk meningkatkan kualitas mereka dalam prosedur belajar-mengajar. Terkait dengan penelitian ini, alat bantu visual direkomendasikan sebagai salah satu dari banyak ilustrator yang dapat digunakan oleh guru untuk menjadi alat alternatif untuk membantu beberapa kesulitan yang ditemukan dalam kegiatan belajar mengajar.